REVISITING QADA’ PRAYERS: An Analytical Study of Classical and Contemporary Islamic Scholars - Najwa Khalilah Harahap; Habiburrahman Rizapoor (Yayasan Nurul Yaqin Annaba, 2025)
Prayer is the second pillar of Islam after the two sentences of the shahada. Prayer holds a crucial position in Islam, as emphasized by the Prophet of Allah. likening it to a pillar for a building, so that a building cannot stand firmly without a supporting pillar. Likewise, a person's Islam will not be strong without upholding prayer. However, sometimes intentionally or not, a Muslim misses prayer until it is out of time. Considering the importance of prayer, can prayers that are left out of time be made up for? In this article presents a discussion of the opinions of ulama regarding making up prayers, along with the arguments regarding the law on making up for prayers, the law on making up for prayers and the types of prayers that can be made up for prayers, as well as the conditions that must be met when making up prayers.